Penggunaan Prefiks pada Teks Biografi Karya Peserta Didik Kelas X SMK Negeri 1 Juwangi Tahun Pelajaran 2020/2021 - Siti Muzaroah; Ika Septiana; Siti Ulfiyani (Jurnal Kualita Pendidikan, 2021)
This study aims to determine the use of prefixes in biographical texts created by students of class X SMK N 1 Juwangi in the 2020/2021 school year. The method in this research is descriptive and equipped with a recapitulation table, with a sample of 43 biographical texts taken randomly from class X TB1 (dressing), TB2, and TBSM3 (motorcycle engineering and business). The data collection technique used in this research is the documentation technique. The results of the use describe the use of prefixes in biographical texts written by students. This is because prefixes are one of the linguistic rules that influence the clarity of information or meaning conveyed by students in biographical texts. Research on prefixes is based on the form of prefixes, namely prefixes {ber}, prefixes {me-}, prefixes {per-}, prefixes {di-}, prefixes {ter-}, prefixes {se-}, prefixes {peN-}, and prefix {to-}. This description can be used as an evaluation material to improve the quality and quality of students' writing skills.